2022
DOI: 10.3389/fbioe.2022.881544
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Bioresponsive Hydrogel Prevents Local Recurrence of Breast Cancer by Enhancing Radiosensitivity

Abstract: Breast cancer is one of the most common types of cancer. Patients are often concerned about regional recurrence after breast cancer surgery. Radiotherapy plays a vital role in reducing recurrence and prolonging the survival of patients undergoing breast-conserving surgery and high-risk mastectomy. However, 8–15% of patients still have disease progression due to radiation resistance. Therefore, new strategies for combination radiotherapy sensitization must be investigated. In this study, an implantable drug loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The CS-FA-MBZ implants effectively inhibited the growth and spread of 4T1 breast tumors 80 . Another study has identified an implantable drug loading system for sunitinib nanoparticles at matrix metalloproteinases-response hydrogel (NSMRH), which uses enzyme-sensitive hydrogel as a carrier to load sunitinib nanoparticles 81 . Animal experiments showed that NSMRH combined with radiotherapy could more effectively control the recurrence of subcutaneous xenograft tumors, prolong the survival time, and have no obvious toxicity in nude mice.…”
Section: Resultsmentioning
confidence: 99%
“…The CS-FA-MBZ implants effectively inhibited the growth and spread of 4T1 breast tumors 80 . Another study has identified an implantable drug loading system for sunitinib nanoparticles at matrix metalloproteinases-response hydrogel (NSMRH), which uses enzyme-sensitive hydrogel as a carrier to load sunitinib nanoparticles 81 . Animal experiments showed that NSMRH combined with radiotherapy could more effectively control the recurrence of subcutaneous xenograft tumors, prolong the survival time, and have no obvious toxicity in nude mice.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the hydrogel can effectively carry radiosensitizers, Chemotherapeutic drugs, photosensitizers and heat-sensitive agents simultaneously. Therefore, the hydrogel systems can not only inhibit the self-replication and random repair of damaged DNA but also effectively alleviate the radiation resistance state of the cancer under hypoxia, which leads to multiple damages to DNA function and enhances the therapeutic effect of brachytherapy ( Chen et al, 2021a ; Fu et al, 2022 ). Wang et al (2021) developed an injectable hydrogel based on Endostatin (ES) and hyaluronic acid-tyramine.…”
Section: Hydrogels Can Be Used In Multiple Treatments For Cancermentioning
confidence: 99%
“…Fu et al. introduced a matrix metalloproteinase (MMP) -responsive hydrogel loaded with sunitinib nanoparticles (NS-MRH) to improve radiosensitivity and prevent local breast cancer recurrence ( 75 ). By being injected into the postoperative cavity and continuously releasing sunitinib, the constructed hydrogel system in this study successfully sensitized radiation and inhibited tumor recurrence.…”
Section: The Application Of Hydrogel-based Local Drug Delivery System...mentioning
confidence: 99%